Institutional Trust 2011 - Holmberg, Sören; Weibull, Lennart; MedieAkademin; TNS Sifo (University of Gothenburg, 2014)
Since 1997, MedieAkademin has carried out an annual survey titled The Institutional Trust. The survey has focused on major social institutions, such as the parliament, big business, the daily press, and TV/radio, as well as some specific companies such as Sveriges Television, TV4, IKEA, Skandia, and Volvo. The number of institutions included has varied somewhat over the years. Some of the institutions and companies have been measured every year while others have been investigated more irregularly.

The survey was carried out by TNS Sifo and involved 1021 individuals who answered a web survey between November 3 and 7, 2011. The 2011 survey also included questions about the media coverage of various institutions and groups, and how the Swedish people view the future of Public Service.

Purpose:

To study the trust that Swedish people have in social institutions, political parties, media, brands/companies, and leaders.

MedieAkademins förtroendebarometer har genomförts årligen sedan 1997. Undersökningen har varje år dels avsett ett urval viktiga samhällsinstitutioner som exempelvis riksdagen, storföretagen, dagspressen och radio-TV, dels ett antal konkreta medier, bl.a Sveriges Television och TV4, och specifika företag, som t ex IKEA, Skandia och Volvo. Antalet bedömda institutioner har varierat något mellan enskilda år. Vissa av institutionerna/medierna/företagen har mätts varje år, andra har studerats mer oregelbundet.

Undersökningen 2011 genomfördes av TNS Sifo under perioden 3/11-7/11 och omfattade 1021 personer som besvarade en nätenkät. I 2011 års undersökning ingick även frågor om massmediernas rapportering om olika institutioner och grupper samt svenskars syn på framtiden av Public Service.

Syfte:

Studera svenska folkets förtroende till samhällsinstitutioner, politiska partier, medier, varumärken/företag och ledare.
Förtroendebarometer 2011
Keywords: mass media; massmedia; trust; förtroende; political attitudes; politiska åsikter; trust in government; förtroende för regeringen; Media; Media; POLITICS; POLITIK; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communications; Medie-, kommunikations-, och informationsvetenskaper